A review of the potential of medicinal plants in the management and treatment of male sexual dysfunction. (29th September 2016) - Malviya, N.; Malviya, S.; Jain, S.; Vyas, S.
Summary: Male sexual dysfunction is a common disorder that appears to be a consequence of a wide range of physical and psychological conditions. Due to mental stress, insufficient physical exercise and various aetiological factors, human being's life is becoming less pleasant, which leads to incapability to have sexual pleasure. The allopathic drugs used for sexual dysfunction are believed to produce a variety of side effects and affect other physiological processes and, ultimately, general health. Therefore, the search for natural supplement from medicinal plants is being intensified probably because of less side effects availability and affordability. Ethnobotanical surveys have indicated a large number of plants traditionally used as aphrodisiacs but only few of them are scientifically validated for the management and treatment of male sexual dysfunction. This article has summarised the medicinal plants traditionally recommended and scientifically validated for the management and treatment of male sexual dysfunction.